Pulmonary function and physical performance in adolescent e-cigarette users: a narrative review - Li, Chen; Guan, Tianyuan (Frontiers in Public Health, 2025)
Adolescent e-cigarette use has risen sharply worldwide and poses emerging threats to respiratory health. As adolescence represents a critical window for lung growth and aerobic capacity, inhalation of toxicants during this period may disrupt pulmonary development and exercise performance. This narrative review synthesizes current evidence on the physiological and behavioral consequences of vaping in youth. Clinical and epidemiological studies indicate that adolescents who vape report higher rates of respiratory symptoms, such as chronic cough, wheezing, and shortness of breath, and may exhibit early declines in lung function and exercise tolerance. Experimental and mechanistic studies implicate nicotine, ultrafine particles, aldehydes, and flavoring agents in oxidative stress, airway inflammation, immune suppression, and impaired alveolarization. Dual users of e-cigarettes and combustible cigarettes appear at even greater risk, with lower cardiorespiratory fitness and muscular endurance compared with non-users. Despite these concerns, research is limited by cross-sectional designs, self-reported data, and a lack of longitudinal cohorts. Further high-quality studies are needed to determine the long-term impact of vaping on adolescent lung development and physical fitness. Preventive efforts in public health, education, and policy are critical to protect youth from the potential pulmonary hazards of e-cigarette use.